Aortic Remodeling as a Prognostic Factor for Late Aortic Events After Thoracic Endovascular Aortic Repair in Type B Aortic Dissection With Patent False Lumen. (August 2014) - Watanabe, Yoshiki; Shimamura, Kazuo; Yoshida, Takuya; Daimon, Takashi; Shirakawa, Yukitoshi; Torikai, Kei; Sakamoto, Tomohiko; Shijo, Takayuki; Toda, Koichi; Kuratani, Toru; Sawa, Yoshiki
Purpose: To assess the significance of aortic remodeling in the prevention of the late aortic events after thoracic endovascular aortic repair (TEVAR) for aortic dissection. Methods: The study involved 52 patients (41 men; mean age was 59.7±13.3 years) with type B aortic dissections and patent false lumens treated with TEVAR between 2004 and 2011. Of the 52 patients, 18 were treated in the acute phase for rupture (n=1), malperfusion (n=10), aortic diameter over 40 mm at onset (n=3), and rapid enlargement of the false lumen (n=4). In the chronic setting, the indications for TEVAR were rupture (n=1), malperfusion (n=2), aortic diameter >50 mm (n=18), and rapid enlargement of the false lumen (n=13). Aortic remodeling was evaluated at 6 months postoperatively, and risk factors for late aortic events were evaluated in multivariate analysis using aortic remodeling and other pre-, peri-, and postoperative factors. Results: Over a mean 36.0±18.9 months, 19 aortic events were documented: enlargement of the false lumen (n=4), type I endoleak (n=2), and erosion at the stent-graft edges (n=13). Multivariate analysis revealed that failure to achieve aortic remodeling at 6 months postoperatively was the only significant risk factor for late aortic events (hazard ratio 0.20, p=0.037). Patients with aortic remodeling had a higher rate of freedom from aortic events compared with those without aortic remodeling (100% vs. 81.5% at 1 year and 79.3% vs. 48.4% at 3 years, respectively). Conclusion: Aortic remodeling after TEVAR is a significant prognostic factor for better long-term results for type B aortic dissection.